Withholding Anticoagulation Following a Single Negative Whole-Leg Ultrasound in Patients at High Pretest Probability for Deep Vein Thrombosis. (January 2013) - Stevens, Scott M.; Woller, Scott C.; Graves, Kencee K.; Aston, Valerie; Jones, Jason; Snow, Gregory; Elliott, C. Gregory
Prompt, accurate diagnosis of deep vein thrombosis (DVT) is essential. A single, whole-leg ultrasound (whole-leg US) has been used to exclude DVT, but limited data exist for patients with high pretest probability (PTP) for DVT. This diagnostic management study tested the rate of venous thromboembolism (VTE) in patients with a PTP of "DVT likely" per the simplified Wells score when anticoagulation is withheld based on a single, negative whole-leg US. Consecutive patients presenting during coordinator shifts with a PTP of DVT likely were enrolled. Anticoagulation was withheld after a single, negative whole-leg US. The outcome was objectively confirmed VTE in 3 months. All 167 patients completed the follow-up. A single patient death was adjudicated as possibly caused by VTE, resulting in a VTE rate of 0.60% (95% confidence interval: 0.02%-3.29%). Whole-leg US should be further studied in diagnostic algorithms that utilize PTP scoring andd -dimer testing.